In Vitro Biological Evaluation and Phytochemical Contents of Three Centaurea L. Species Growing from Eastern Anatolia in Turkey - Keser, Serhat; Keser, Fatma; Turkoglu, Ismail; Kaygili, Omer; Tekin, Suat; Demir, Ersin; Turkoglu, Semra (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2020)
Centaurea L. species were used as medicinal plants among the people for treatment of the common cold, abscesses, peptic ulcers, hemorrhoid and diabetes etc.. In the present study, antiradical properties, phytochemical contents, antimicrobial and antiproliferative activities of three Centaurea species were investigated. Centaurea saligna (K.Koch) Wagenitz methanol (99.94%), Centaurea virgata Lam. methanol (98.23%) and water (98.10%) extracts were showed higher ABTS scavenging than trolox (96.79%). Centaurea kurdica Reichardt extracts showed lower activity than trolox for all the antiradical assays. Centaurea extracts exhibited antimicrobial activity against to some microorganisms. It was determined that these Centaurea species contain high amount of total flavonoid, phenolic and proanthocyanidin, phenolic acids, phytosterols and unsaturated fatty acids. Also, three Centaurea extracts showed very high antiproliferative property on LNCaP, HCT-116, MCF-7 cancer cell lines.
Keywords: Centaurea; Endemic; Antiradical; Phytochemical; Antiproliferative